Role of Public Investment in Growth and Poverty Reduction in Transition Economies - Acharya, Sanjaya; Nuriev, Shamshimukhamed (Journal of Reviews on Global Economics, 2016)
This paper explores the linkages among public investment, growth and poverty in light of the existing theories, evidence and methods for 30 transition economies using the panel data for 1995-2010. Using Least Square Dummy Variable technique, we conclude that public investment is growth enhancing; furthermore, the impact is even higher if associated with foreign direct investment. However, public investment is still not strong enough to reduce poverty, poverty gap and inequality in income distribution. In case of the latter, it has rather worsening impact. But if public current expenditure is spent primarily on educational subsidies, this brings pro-poor growth impact.